Testing for long-run purchasing power parity of Asean4-Singapore through the impact of cept scheme and global financial crisis / Abdul Rahim Ridzuan and Maizatul Saadiah Mohamad - Ridzuan, Abdul Rahim; Mohamad, Maizatul Saadiah (Research Management Institute (RMI), 2011)
This paper examines the validity of purchasing power parity (PPP) hypothesis for four founding members of the Association of Southeast Asian Nations (ASEAN4) with Singapore as base currency. A range of standard unit root tests and cointegration used in previous studies applied to test long run PPP and four models are introduced based on the implementation of Common Effective Preferential Trade (CEPT) scheme and the impact of global financial crisis. The result from the unit root test showed that all the data are stationary at I (1). Therefore, the data fulfill the requirement to proceed with the Johansen Juselius cointegration test. There is no evidence of PPP detected between ASEAN4 and Singapore before the implementation of CEPT scheme in model 1. This may due to the existence of tariff and non-tariff barriers of the good and services among the ASEAN4 and Singapore that leads to a failure of PPP theory. However, the evidence of long-run PPP is detected between Malaysia-Singapore, Thailand-Singapore and Philippines- Singapore after the implementation of CEPT scheme for model 2 and before the global financial crisis hits in U.S economy. Among these three countries, the strongest presence of PPP is found between Malaysia and Singapore where it carried both correctly signed and statistically significant variables. While the evidence of PPP for Thailand and the Philippines seems weaker due to it's contradict expected sign. In Model 3, the existence of PPP is strongly detected for Malaysia-Singapore, white weakly detected for Philippines-Singapore during the global financial crisis. The strong evidence of PPP at this period suggest that the Malaysia' economy is still strong enough to cushion the effect of this recession due to its diversification economic policy. In Model 4, we fail to detect any evidence of PPP for ASEAN4- Singapore. This prove that the ASEAN4-Singapore countries still in the progress of recovery after global recession which lead to the failure of PPP. Field of research: International Economics